2006
DOI: 10.1111/j.1551-2916.2006.01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Indentation Induced FE‐to‐AFE Phase Transformation in Lead Zirconate Titanate

Abstract: Instrumented indentation was combined with microscopy and spectroscopy analysis to investigate the local mechanically induced ferroelectric to anti‐ferroelectric phase transformation of niobium‐modified lead zirconate titanate 95/5. Indentation experiments to a depth of 2 μm were performed using a Berkovich pyramidal three‐sided diamond tip. Subsequent Raman spectroscopy and piezoelectric force microscopy revealed that indentation locally induced the ferroelectric to antiferroelectric phase transformation. Pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Indentation‐induced ferroelectric‐to‐antiferroelectric phase transformation has recently been observed in a ferroelectric lead zirconate titanate ceramic with a composition close to the ferroelectric/antiferroelectric phase boundary 28 . As the ferroelectric phase in these oxides displays a larger molar volume than the antiferroelectric phase, 23,24,29 this transformation corresponds to a volume contraction and hence undermines the fracture resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indentation‐induced ferroelectric‐to‐antiferroelectric phase transformation has recently been observed in a ferroelectric lead zirconate titanate ceramic with a composition close to the ferroelectric/antiferroelectric phase boundary 28 . As the ferroelectric phase in these oxides displays a larger molar volume than the antiferroelectric phase, 23,24,29 this transformation corresponds to a volume contraction and hence undermines the fracture resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Indentation-induced ferroelectric-to-antiferroelectric phase transformation has recently been observed in a ferroelectric lead zirconate titanate ceramic with a composition close to the ferroelectric/antiferroelectric phase boundary. 28 As the ferroelectric phase in these oxides displays a larger molar volume than the antiferroelectric phase, 23,24,29 this transformation corresponds to a volume contraction and hence undermines the fracture resistance. In the current PNZST 43/12/2 ceramic specimen, the ferroelectric-to-antiferroelectric transformation may not occur as the composition is quite away from the phase boundary (According to He and Tan, 27 the phase boundary at room temperature roughly corresponds to PNZST 43/8/2.).…”
Section: Discussionmentioning
confidence: 99%
“…However, the two splitting peaks are incorporated in the PNZTM95/5 ceramics. Being very near to the FE/AFE phase boundary, PNZT95/5 has been known to be in the ferroelectric phase at room temperature [5]. It is reasonable to speculate that the PNZT95/5 and PNZTM95/5 ceramics belong to the ferroelectric phase at room temperature.…”
Section: Methodsmentioning
confidence: 98%
“…Based on the symmetry-conforming principle of point defects, the domain stabilization is a volume effect in the ferroelectrics [12]. This theory could well explain the differences of the P-E loops between the acceptor doped ferroelectric and the normal ferroelectric [5,12,13]. Ren et al has suggested that in the acceptor element Mn doped BaTiO 3 , the defect ions Mn 3+ and the O 2À vacancies form defect dipoles to pin the migration of ferroelectric dipoles and induce double hysteresis loops [6,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation